Lingual haemangiosarcoma in a crossbred dog - Owen Laura J; Grierson James M; Patterson-Kane Janet C; Baines Stephen J (Irish Veterinary Journal, 2006)
Abstract An eight-year-old, male neutered, crossbred dog was presented for investigation of a lingual mass of four months duration. Oral examination revealed a 7 cm × 5 cm soft, fluctuant mass at the caudal aspect of the tongue. Ultrasound examination of the mass demonstrated mixed echogenicity, with cavitations containing hypoechoic and anechoic regions. Lingual haemangiosarcoma was diagnosed on histopathological examination of multiple biopsy samples, with confirmation of the vascular endothelial origin of tumour cells by positive immunolabelling for factor VIII-related antigen.